2014
DOI: 10.1007/s11033-013-2937-0
|View full text |Cite
|
Sign up to set email alerts
|

Association of four insulin resistance genes with type 2 diabetes mellitus and hypertension in the Chinese Han population

Abstract: Insulin resistance plays an important role in the development of type 2 diabetes mellitus (T2DM) and hypertension. The purpose of the present study was to evaluate the association between four insulin resistance genes (ADIPOQ, LEPR, RETN, and TRIB3) and both T2DM and hypertension. A total of 768 Han Chinese subjects were recruited into this study, including 188 cases who had T2DM alone, 223 cases who had hypertension alone, 181 cases with both T2DM and hypertension, and 176 control subjects with neither T2DM n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 55 publications
2
24
0
Order By: Relevance
“…In our population, however, there were no differences in either genotype distribution or allelic frequencies for both polymorphisms examined between the Control group and the obesity or the T2D groups; therefore, no associations were found in any of the genetic models. These results were in accordance with previous reports for Asians, Northern Americans, and Europe [21,23,24,36,37,[39][40][41][42][43]45,46]. However, two studies, conducted in Asians [8] and Africans [9] population have shown an increased risk of developing T2D related to the g.-420C>G mutation.…”
Section: T2d Is a Leading Cause Of Morbidity And Mortality Among Adultssupporting
confidence: 92%
See 1 more Smart Citation
“…In our population, however, there were no differences in either genotype distribution or allelic frequencies for both polymorphisms examined between the Control group and the obesity or the T2D groups; therefore, no associations were found in any of the genetic models. These results were in accordance with previous reports for Asians, Northern Americans, and Europe [21,23,24,36,37,[39][40][41][42][43]45,46]. However, two studies, conducted in Asians [8] and Africans [9] population have shown an increased risk of developing T2D related to the g.-420C>G mutation.…”
Section: T2d Is a Leading Cause Of Morbidity And Mortality Among Adultssupporting
confidence: 92%
“…Five studies were not written in English or Spanish, six lacked sufficient information, seven were not case-control studies, two were duplicate studies, three considered different BMI cutoffs for obesity, and one focused on children and were therefore excluded (Figure 1). From the remaining twenty-eight studies, eighteen focused on the g.-420C>G polymorphism [8,9,19,21,[23][24][25][26][35][36][37][38][39][40][41][42][43][44] and four on the c.+62A>G polymorphism [22,25,45,46]. Our current study was also considered for the meta-analysis.…”
Section: Characteristics Of the Studies From Literature Reviewmentioning
confidence: 99%
“…BMI and WHR have been associated with hypertension, DM, and cardiovascular diseases, and act as risk factors for metabolic syndromes (Fasanmade et al, ; Jiang, Liu, Fang, Wang, & Li, ; Marcadenti et al, ; Zanella, Kohlmann, & Ribeiro, ). Previously, Jiang et al () reported that factors such as age, sex, BMI, levels of high density lipoprotein (HDL), low density lipoprotein (LDL), total cholesterol, and TG are associated with hypertension in patients with T2DM. Fasanmade et al () also reported that significantly higher age, mean BMI, waist circumference, and WHR were seen in patients with T2DM along with hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…ANOVA showed influence of Gln allele of rs1137101 polymorphism of LEPR gene (Table 3) Listed changes are traditionally linked with obesity in patients with DM2 [8,9] and presented in the table 3 according to decrease of influence degree of alleles of rs1137101 polymorphism of LEPR gene: increase of BMI > hyperleptinemia > dyslipidemia (increase of triglycerides and decrease of protective HDL), which were on the background of increase of insulin resistance.…”
Section: Resultsmentioning
confidence: 99%
“…Numeral data [8][9][10] shows that rs1137101 polymorphism of LEPR gene leads to disorder of structure and function of leptin receptor and blocks its expression with alteration of hormonal signal. We suggest that presence of allele Gln in genotype contributes increase of BMI, HOMO, leptin and triglyceride level, and decrease protective HDL.…”
Section: Resultsmentioning
confidence: 99%